2016
DOI: 10.1088/1752-7155/10/4/046010
|View full text |Cite
|
Sign up to set email alerts
|

Limonene in exhaled breath is elevated in hepatic encephalopathy

Abstract: Breath samples were taken from 31 patients with liver disease and 30 controls in a clinical setting and proton transfer reaction quadrupole mass spectrometry (PTR-Quad-MS) used to measure the concentration of volatile organic compounds (VOCs). All patients had cirrhosis of various etiologies, with some also suffering from hepatocellular cancer (HCC) and/or hepatic encephalopathy (HE). Breath limonene was higher in patients with No-HCC than with HCC, median (lower/upper quartile) 14.2 (7.2/60.1) versus 3.6 (2.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 56 publications
6
42
0
Order By: Relevance
“…The unbalanced sex ratio within each group reflects the higher prevalence of HCC in male patients ( 26 ). Across all subjects, the exhaled limonene levels were not affected by sex ( P value = 0.308), as previously described ( 17 , 27 ). Significant differences in age were observed between the study groups ( P values: 0.019, 0.006, and 0.0002, respectively, for cirrhosis vs healthy, HCC+cirrhosis vs healthy, and cirrhosis vs HCC+cirrhosis).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The unbalanced sex ratio within each group reflects the higher prevalence of HCC in male patients ( 26 ). Across all subjects, the exhaled limonene levels were not affected by sex ( P value = 0.308), as previously described ( 17 , 27 ). Significant differences in age were observed between the study groups ( P values: 0.019, 0.006, and 0.0002, respectively, for cirrhosis vs healthy, HCC+cirrhosis vs healthy, and cirrhosis vs HCC+cirrhosis).…”
Section: Resultssupporting
confidence: 81%
“…This reduction is attributed to the downregulation of CYP2C9 and CYP2C19, which, in turn, increases the half-life of limonene in the bloodstream, leading to higher abundance in the breath ( 13 18 ). O'Hara et al ( 17 ) found a moderate increase of breath limonene in patients affected by HCC with underlying cirrhosis. Furthermore, proteomic profiling of resected early-stage liver primary tumors and comparison with paired non-tumor liver tissues showed a general downregulation of the CYP 450 system, including CYP2C9 and CYP2C19, in the cancer tissues ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Limonene is a monoterpene contained in most plant-based foods, especially citrus fruits. High limonene secretion in the breath of cirrhotic patients is the result of reduced limonene clearance from the bloodstream due to dysfunctional biotransformation in the liver [72,74]. These results suggest that exogenous limonene introduced through diet could reveal differences in liver function via measurement of limonene secretion in breath.…”
Section: Exogenous Vocs In Breath Analysis For Health and Diseasementioning
confidence: 94%
“…The evidence mentioned above about the association between breath levels of limonene and liver dysfunction [72,74] as well as other studies that clearly indicates that washout curves of administered exogenous VOCs can be used for assessing metabolic function and pharmacokinetics in vivo [93,94]. Yet, the inability to control limonene intake in the general population complicates the definition of threshold values of breath limonene for the identification of liver dysfunction in this application.…”
Section: Exogenous Voc (Evoc) Probes For In Vivo Metabolic Phenotypingmentioning
confidence: 99%
“…Proton Transfer Reaction Time-of-Flight Mass Spectromery (PTR-ToF-MS) is a real-time technique, capable of simultaneously measuring the evolution of multiple gas metabolites from a single breath. It has been used for the identification of potential useful VOC biomarkers for diagnosis of a variety of diseases including various cancers,63–65 liver disease66 67 and respiratory disease 68. It has several advantages in clinical settings, such as the speed of sampling, the instant result achieved and the lack of need for sample storage or shipping.…”
Section: Breath Profilingmentioning
confidence: 99%